Adverbial modification of a proposition: types of situations defined, possibilities and limitations - Golubeva, Victoria K. (Journal of the Belarusian State University. Philology, 2025)
Syntactic structures with predicatives that attach a propositional actant expressed by an infinitive construction or a dependent clause and utterances with sentential adverbs that define the whole situation rather than a specific aspect of the verb action are analysed. Predicatives and sentential adverbs due their ability to modify the proposition are considered as means capable of forming semantically equivalent structures. The types of correlation between predicatives and propositions in dependent clauses (the predicative evaluates the controlled action of the person represented in the proposition; the predicative qualifies the possibility or expediency of the situation without regard to one’s actions, expressed in the proposition; the predicative characterises the proposition with an inanimate participant or a personal subject and a spontaneous situation connected with it; the predicative evaluates two interrelated propositions represented in conjunct clauses) are distinguished. The possibility of the predicate combined with the infinitive and the sentential adverb to form synonymous utterances within these types of correlation are revealed.